Brexit and Impact on Immigration to the UK - MATMATI, Halima (My University, 2017)
The thesis discusses the impact of brexit on immigration. First the development of immigration in UK especially in Great Britain from the celtic and pict tribes when they arrived and formed the first communities in the British Isles until 2000, when the growth of asylum seeker applications contributed to a new growth of immigration to the UK. But the rise in asylum seeker arrivals has seen a rise in racial tensions. Fifty years after the start of mass immigration to the UK, and from the EU, immigration was arguably the biggest issue driving the Leave campaign, with many Britons saying that they wanted to see a reduction in the number of migrants.
Keywords: Great Britain; Brixit; Immigration; Impact; Issue